2017
DOI: 10.1038/s41540-017-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the traditional Japanese medicine “Kampo”: compounds, metabolites and pharmacological profile of maoto, a remedy for flu-like symptoms

Abstract: Pharmacological activities of the traditional Japanese herbal medicine (Kampo) are putatively mediated by complex interactions between multiple herbal compounds and host factors, which are difficult to characterize via the reductive approach of purifying major bioactive compounds and elucidating their mechanisms by conventional pharmacology. Here, we performed comprehensive compound, pharmacological and metabolomic analyses of maoto, a pharmaceutical-grade Kampo prescribed for flu-like symptoms, in normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…A clinical study reported that glychyrrhetinic acid can be detected 3 h or more after administration of licorice root containing the Kampo medicine, rikkunshito (Kitagawa et al 2015 ). Additionally, we have evaluated some herbal medicines in mice and rats using plasma metabolome analysis (Ohbuchi et al 2015 ; Nishi et al 2017 ). In these studies, a number of metabolites significantly changed at 2–4 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study reported that glychyrrhetinic acid can be detected 3 h or more after administration of licorice root containing the Kampo medicine, rikkunshito (Kitagawa et al 2015 ). Additionally, we have evaluated some herbal medicines in mice and rats using plasma metabolome analysis (Ohbuchi et al 2015 ; Nishi et al 2017 ). In these studies, a number of metabolites significantly changed at 2–4 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results suggest that there exists a metabolite-level property that is particularly based on the in natura state of culture condition, which has been generally treated as the irreplaceable support of the whole food quality that cannot be produced with synthetic nutritional supplements. Generally, the health effects of plant products cannot be totally evaluated with a single component, but should be considered within the whole diet composed of many compounds acting synergistically on human health [52,53]. The intrinsic distribution of compounds particular to in natura metabolite should further be considered when evaluating the sustainability of food systems toward the resolution of the health-diet-environment trilemma [3].…”
Section: Discussionmentioning
confidence: 99%
“…One animal (n = 1) at a time was sacrificed 1 h post-drug administration under anesthesia with isoflurane by collecting whole blood from the abdominal inferior vena cava using an EDTA-2K treated syringe. According to previous pharmacokinetic studies of herbal medicines [ 33 , 58 ], many of the components were quickly absorbed into the bloodstream, thereby providing the rationale for a sampling time at 1 h. Blood was centrifuged at 1200× g at 4 °C for 30 min to obtain plasma; then, the sample was stored at −80 °C until LC-HRMS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Occasionally, in vitro pharmacological experiments involving herbal medicine are conducted by direct exposure to rodent or human cell lines. However, this method might be unsuitable for understanding the precise action of medicines, as many ingredients within herbal medicines are not absorbed as their intact form [ 33 ]. Therefore, we performed a pharmacokinetic study utilizing the non-targeted analysis to explore the bioavailable ingredients of AR using rats, prior to performing the pharmacological study.…”
Section: Introductionmentioning
confidence: 99%